2023
DOI: 10.1038/s41586-023-06158-6
|View full text |Cite
|
Sign up to set email alerts
|

A massive quiescent galaxy at redshift 4.658

Abstract: The extremely rapid assembly of the earliest galaxies during the first billion years of cosmic history is a major challenge for our understanding of galaxy formation physics1–5. The advent of the James Webb Space Telescope (JWST) has exacerbated this issue by confirming the existence of galaxies in substantial numbers as early as the first few hundred million years6–8. Perhaps even more surprisingly, in some galaxies, this initial highly efficient star formation rapidly shuts down, or quenches, giving rise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…JWST/NIRSpec deepspectroscopic observations have confirmed the candidate in Onoue et al (2023) at z spec = 5.2 by detecting a broad Hα emission line that indicates a black hole mass of M BH ∼ 10 7 M e , with an additional finding of a red AGN at z spec = 5.6 (Kocevski et al 2023). NIRSpec spectroscopy has also identified an SMBH in a quiescent galaxy at z = 4.658 (Carnall et al 2023). NIRSpec IFU observations have revealed broad Hα and Hβ emission lines in a galaxy at z = 5.55 (Übler et al 2023), which is interpreted as a type 1.8 AGN with a black hole mass of M BH ∼ 10 8 M e .…”
Section: Introductionmentioning
confidence: 86%
“…JWST/NIRSpec deepspectroscopic observations have confirmed the candidate in Onoue et al (2023) at z spec = 5.2 by detecting a broad Hα emission line that indicates a black hole mass of M BH ∼ 10 7 M e , with an additional finding of a red AGN at z spec = 5.6 (Kocevski et al 2023). NIRSpec spectroscopy has also identified an SMBH in a quiescent galaxy at z = 4.658 (Carnall et al 2023). NIRSpec IFU observations have revealed broad Hα and Hβ emission lines in a galaxy at z = 5.55 (Übler et al 2023), which is interpreted as a type 1.8 AGN with a black hole mass of M BH ∼ 10 8 M e .…”
Section: Introductionmentioning
confidence: 86%
“…These exceptional discoveries come on top of more numerous detections in the redshift range z = 4-7 (i.e., where the Hα line is effective in measuring masses) that is filling the 10 6 -10 8 M e black hole mass range (Carnall et al 2023;Harikane et al 2023a;Kocevski et al 2023;Onoue et al 2023;Übler et al 2023). This redshift range is now filled with many galaxies hosting black holes, also of low mass, that allow some statistical inference.…”
Section: Introductionmentioning
confidence: 97%
“…This AGN candidate, CEERS-AGN-z5-1, has a compact morphology and shows a rest-frame UV-to-optical spectral energy distribution (SED) that can be well explained by an unobscured quasar with L bol = (2.5 ± 0.3) × 10 44 erg s −1 and strong Balmer and [O III] emission lines. In addition, Carnall et al (2023) recently reported the detection of broad Hα emission from a quiescent galaxy at z = 4.658 using JWST, from which they measure the central SMBH mass of M BH = 10 8.7±0.1 M e .…”
Section: Introductionmentioning
confidence: 99%